Voting, Contagion and the Trade-Off between Public Health and Political Rights: Quasi-Experimental Evidence from the Italian 2020 Polls - Marco Mello; Giuseppe Moscelli (Institute of Labor Economics (IZA), 2021)
We exploit a quasi-experimental setting provided by an election day with multiple polls to estimate the effect of voters' turnout on the spread of new COVID-19 infections and to quantify the policy trade-off implied by postponing elections during high infection periods. We show that post-poll new COVID cases increased by 1.1% for each additional percentage point of turnout. The cost-benefits analysis based on our estimates and real political events shows that averting an early general election has saved Italy up to about e362 million in additional hospital care costs and e7.5 billion in values of life saved from COVID.
Keywords: C23; D72; H51; I18; 330; control function; endogeneity; event-study; public health; civic capital; voting; COVID-19